2021
DOI: 10.3390/ijerph18168417
|View full text |Cite|
|
Sign up to set email alerts
|

Sailors and the Risk of Asbestos-Related Cancer

Abstract: Sailors have long been known to experience high rates of injury, disease, and premature death. Many studies have shown asbestos-related diseases among shipyard workers, but few have examined the epidemiology of asbestos-related disease and death among asbestos-exposed sailors serving on ships at sea. Chrysotile and amphibole asbestos were used extensively in ship construction for insulation, joiner bulkhead systems, pipe coverings, boilers, machinery parts, bulkhead panels, and many other uses, and asbestos-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…In addition to tobacco, which causes 92% of all lung cancers in industrialized countries [25] , some occupational exposures may explain part of the elevated cancer mortality rates. For example, in land transport, seafaring, and defense forces diesel engine exhaust [ 26 , 27 ] and in seafaring also asbestos [28] may contribute to the elevated cancer risk. A recent systematic review showed, compared with non-drivers, an 18% increased risk of lung cancer among professional drivers who are potentially exposed to diesel exhaust, after adjustment for the confounding effect of smoking [27] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to tobacco, which causes 92% of all lung cancers in industrialized countries [25] , some occupational exposures may explain part of the elevated cancer mortality rates. For example, in land transport, seafaring, and defense forces diesel engine exhaust [ 26 , 27 ] and in seafaring also asbestos [28] may contribute to the elevated cancer risk. A recent systematic review showed, compared with non-drivers, an 18% increased risk of lung cancer among professional drivers who are potentially exposed to diesel exhaust, after adjustment for the confounding effect of smoking [27] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the list of high-risk non-asbestos occupations is not-exhaustive as recent evidence highlights. A comprehensive review of published epidemiologic studies indicated that sailors are also at high risk of asbestos-related diseases and demonstrate elevated morbidity and mortality from mesothelioma and other ARDs [ 53 ].…”
Section: Exposure Pathwaysmentioning
confidence: 99%
“…There was an error in the original article [ 1 ]. The error concerned the unit of air when referring to the standard of 2 million asbestos fibers longer than 5 microns in length.…”
Section: Text Correctionmentioning
confidence: 99%